If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9p + 8p = 0 Combine like terms: 9p + 8p = 17p 17p = 0 Solving 17p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '17'. p = 0 Simplifying p = 0
| 2+6(t-4)=4(t-6)+8 | | y+4-4=3x-9-4 | | 4q+6=-3q-43 | | -2m+7=2m-1 | | 5h=4x | | 8e-3=5e-9 | | 17d-3=9d+45 | | 2p+9=6p-27 | | 9t+10t=38 | | -c+2=-6c-13 | | 654/15 | | -2w+1=-7w+41 | | 5h=3x+150 | | -2f-6=-5f-3 | | 11d+5=3d-3 | | 7z-6=3z+4 | | -8k+4=-6k+20 | | 9j-4=5j+28 | | -6u+7=u+70 | | y/5=-20 | | 11u+1=6u-29 | | -x-4=-4x+2 | | -8g+7=-g+63 | | 70=6x-14 | | 7j-4=3j-28 | | 10e-4=4e-10 | | 2a+4=-3a-36 | | -2q+6=3q-24 | | 2x-1=-x-28 | | 6h-4=h-9 | | 9y-1=5y+15 | | 12+8=5d+57 |